Evaluation of Light-Activated Provisional Resin Materials for Periodontal Soft Tissue Management. (8th September 2016) - Jun, Soo-Kyung; Lee, Hae-Hyoung; Lee, Jung-Hwan
Abstract : The purpose of this study was to determine mechanical properties using a compressive test with cylinder specimen (h = 6 mm and ϕ = 4 mm) as well as cytotoxicity using elutes from disk specimen (ϕ = 10 mm and h = 2 mm) against human gingival fibroblasts and oral keratinocytes with light-activated provisional resin materials (Revotek LC and Luxatemp Solar) compared to chemically activated counterpart (Snap, Trim II, and Jet). Significantly increased compressive strength (210 280 MPa) was detected in light-activated products compared to chemically activated ones (20 65 MPa, P < 0.05 ) and similar compressive modulus was detected in both types (0.8 1.5 and 0.5 1.3 GPa). Simultaneously, the light-activated products showed less adverse effects on the periodontal soft tissue cells in any polymerization stage compared to the chemically activated products. Particularly, chemically activated products had significantly greater adverse effects during the "polymerizing" phase compared to those that were "already set" (P < 0.05 ), as shown in confocal microscopic images of live and dead cells. In conclusion, light-activated provisional resin materials have better mechanical properties as well as biocompatibility against two tested types of oral cells compared to the chemically activated counterpart, which are considered as more beneficial choice for periodontal soft tissue management.